2022
DOI: 10.3390/agronomy12112655
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis and Optimization for Steering Motion Mode Switching of an Agricultural Four-Wheel-Steering Mobile Robot

Abstract: This study focuses on a wheeled mobile robot used for detection, weeding and information monitoring in agriculture. However, it is difficult to reach satisfactory motion mode switching (MMS) performance. This paper aimed at exploring the optimal control parameters guaranteeing smooth MMS of four-wheel steering. Single factor tests were first conducted using a test-bench. A binary quadratic general rotation combination test was designed to obtain the optimal parameters. An entropy weight method was introduced t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Typically, grassy terrain can be difficult for Mecanum wheels owing to its unevenness. To achieve better performance on rough terrains, Reina et al [ 29 ] and Qu et al [ 30 ] proposed a four-wheel-drive/four-wheel-steer robot. The corresponding experiment indicated that the proposed robot could be used on an all terrains for agriculture.…”
Section: Related Studiesmentioning
confidence: 99%
“…Typically, grassy terrain can be difficult for Mecanum wheels owing to its unevenness. To achieve better performance on rough terrains, Reina et al [ 29 ] and Qu et al [ 30 ] proposed a four-wheel-drive/four-wheel-steer robot. The corresponding experiment indicated that the proposed robot could be used on an all terrains for agriculture.…”
Section: Related Studiesmentioning
confidence: 99%
“…Sun [20] designed a six-wheel full-driving wheel chassis and conducted dynamic simulations on its obstacle crossing performance, as well as the mechanical state simulation of the four-wheel and six-wheel model with or without suspension conditions, the parameterized analysis was used to optimize the forward speed of the six-wheel independent suspension chassis and to optimize the spring stiffness of the suspension system, the prototype was built to verify the feasibility of the four motions including bottom linear motion, zero-radius rotation motion, climbing motion and obstacle-crossing motion. Qu et al [21] constructed a steering coordination control strategy for wheel-to-wheel following linkage on a four-wheel independent steering chassis driven by the hub motor, and the prototype road validation experiment was conducted based on the software and hardware design of the steering control system. Qin et al [22] innovatively designed a multi suspension wheeled chassis and compared and analyzed the obstacle-crossing height and climbing angle by establishing the mathematical models of multi suspension and traditional structure chassis.…”
Section: Introductionmentioning
confidence: 99%